Revealing the Li2O2 nucleation mechanisms on CeO2 catalysts for lithium‐oxygen batteries - Cortés Páez, Henry Andrés (2020)
The addition of ceria (CeO2) nanoparticles to the cathode of a lithium-oxygen battery results in increased capacity, lower overpotentials and better cyclability. To shed light on the mechanisms of this performance enhancement, we have investigated the early stages of Li2O2 nucleation at stoichiometric and reduced ceria surfaces by means of atomistic simulations based on density functional theory. Adsorption energies are stronger on ceria than on graphene, that is, nucleation mainly would take place on the oxide. The adsorption process of O2 is the one that determines the nucleation sites for the Li2O2 formation on the different CeO2 surfaces. The LiO2 intermediate is adsorbed at the O2 reduction sites. On the reduced (100) surface, the LiO2 tends to adsorb dissociatively, opening up the possibility to the formation of other species than the desired end-product, Li2O2. On the contrary, optimal properties are found for the reduced (110) surface, which should therefore be the most active surface for Li2O2 nucleation among all low-index surfaces of ceria. These findings could pave the route to produce better cathodes for Li-oxygen batteries by the addition of carefully designed ceria nanoparticles, which maximizes the exposition of the most favorable facet.